A wake detector for wind farm control. (June 2015) - Bottasso, C L; Cacciola, S; Schreiber, J
Abstract: The paper describes an observer capable of detecting the impingement on a wind turbine rotor of the wake of an upstream machine. The observer estimates the local wind speed and turbulence intensity on the left and right parts of the rotor disk. The estimation is performed based on blade loads measured by strain gages or optical fibers, sensors which are becoming standard equipment on many modern machines. A lower wind speed and higher turbulence intensity on one part of the rotor, possibly in conjunction with other information, can then be used to infer the presence of a wake impinging on the disk. The wake state information is useful for wind plant control strategies, as for example wake deflection by active yawing. In addition, the local wind speed estimates may be used for a rough evaluation of the vertical wind shear.